STRATEGI MEMBANGUN DESA MANDIRI MELALUI OPTIMALISASI PEMANFAATAN DANA DESA (DD) BERBASIS LOKALITAS DI KABUPATEN BUTON SELATAN LOCALITY-BASED RURAL BUILDING STRATEGY THROUGH OPTIMIZATION USING LOCALITY-BASED FUNDS (DD) IN SOUTH BUTON DISTRICT SOUTHEAST - Haq, Dais (Jurusan Pendidikan Sejarah, Universitas Halu Oleo, 2020)
ABSTRACTThis research aims to formulate the idea of optimizing rural government fund (DD) management, to realize an independent and ability village in South Buton District.Â The main focus of this research is first, to analyze the potential and problems of village funds in South Buton District. Second, to formulate a strategic program design for optimizing rural fund management in an effort to create an independent and abilityÂ rural. This study uses two data sources, namely perimer and secondary data Perimer data were obtained from interviews and discussions with DD managers in Batauga and Sampolawa Subdistricts of Buton Selatan District. Data collection took place from December 2018 to February 2019 using interviews and informal discussions. The results of this study are DD Management Strategies in an effort to realize the independence and welfare of rural communities in South Buton